Paisagem cárstica e turismo no estado de Sergipe - Santos, Jorgenaldo Calazans dos (2019)
Sergipe’s karstic landscape has drawn people’s attention to its potential for tourism. This has raised a concern as to the way touristic practices are being developed, since there have been no in-depth studies on the issue. Thus, in this work, we analyze the socio-spatial relations that were established in the karstic landscape in order to measure its potential for tourism, especially through the relationships of those individuals who inhabit the surroundings of the caves. From these references, we observed the karstic landscape from the strand of geotourism that bases itself on the principles of sustainability. As a result, the hypothesis we have raised is based on the prerogative of the cultural landscape, and it argues that the karstic caves of the State of Sergipe have the necessary attributes to serve as a resource for geotourism practice. To this end, we have carried out a field research, in which we observed a pre-established script and photographic records. We have selected six caves to be part of the study, by taking into account their infrastructure, proximity, inner beauty, extension and availability for visitation. Based on such criteria, we visited the following caves: Casa do Caboclo (or Caboclo’s House), located in the municipality of Japaratuba; Matriana, Pedra Furada (or Pierced Rock) and Pedra Furada II (or Pierced Rock II), located in the municipality of Laranjeiras; Dorinha and Toca da Raposa (or Fox’s Den), located in the municipality of Simão Dias. The analyses were guided by the theories of Cultural Geography, according to Sauer (2004, 2006), Berque (2004), Besse (2006), Dardel (2011), Almeida (2003, 2004, 2008), Leff (2001, 2004) and Sachs (1994, 2002, 2004, 2007). At the end of the study, we realized that there is potential for the development of geotourism in these locations, which has aroused, in particular, the interest of travel agencies in developing tourism in the caves.